Desain Sistem Informasi Akuntansi (Studi kasus: Perusahaan Pada Industri Perikanan) - Eric Robert Sarwono; Maria Angelina Eklesia Senewe; Ika Prayanthi (CogITo Smart Journal, 2022)
This study aims to evaluate and provide recommendation about the implementation of Accounting Information System related to the components and the procedures in the respective business cycle. The object of this research is PT. YYY, a company engage in the fishing industry. The method conducted in this research is descriptive qualitative with a case study. The data collection process is taken from observations and interviews. This study compares theory and practice in PT. YYY with the purpose of providing recommendation for future development. By using the Accounting Information System theory as the benchmark we suggest the company to use a cloud-based Accounting Information System. We recommend Odoo Software as one of the great options, as Odoo have the standardized Accounting Information System components and features. Implementing this platform could help the company to improve its Accounting Information System, as it is such a crucial and fundamental component that the company ought to have to be able to sustain and grow in the future